A institucionalização da justiça na sociedade bem-ordenada: Construtivismo constitucional, razão pública e legitimidade democrática - Lima Júnior, André Luiz Silveira De (Universidade do Vale do Rio dos Sinos, 2017)
The main theme of this paper is the question of Justice, established through a resumption of fundamental principles, shows that the directions of the formation and maintenance of society were made with the settlement of their terms by the criteria of ratification of the righteous. In view of Western tradiction, which is linked to the social contract specifically under the aegis of liberalism, the search for a resurgence of the genealogical elements of Modern State was sought from the interconnection between the values of freedom and equality. However, it is quite true that history has shown that this paradigm, despite all the expectation in the belief of answers proposed by scientific methods, not only proved be incapable of overcoming the material inequalities, but also legitimized, in the unrestricted trust in legality, acts of inhumanity that conform an “aesthetics of destruction”. The resumption of the human rights paradigm, after mid-twentieth century, allowed a return of morality to institutional elements of social cooperation, linked by a creation of a supranational system, responsible for the formation of an international federation seeking for the sublimation of dignity. Nonetheless, national sovereignty remained in vogue, but with constitutional foundations. But, even at this point, was still lacking of a theory that could mediate the Democratic Rule of Law with the new epistemological resizing, especially when there is a latent pluralism, reverberate by the approximation of different cultures in globalization. What would be the best way to allow individuals to “(re)ex(s)ist”, while maintaining their autonomy when sharing the same horizon within other members of society? The hypothesis, confirmed in the conclusion, is that the model of political liberalism, proposed by John Rawls and structured from justice as fairness, in which the liberal principles (of the maximum individual freedom and of the difference) provide the bases for the concatenation of a deliberative democracy, although it has gaps to be improved, is the closest to solving the problem by concrete answers. This is because it seeks to benefit all members, making their terms rational in a decision which opt out to make a rationalization of justice terms and also respecting the public reason allowing the existence of the most diverse doctrines.
Keywords: Teoria da justiça; Liberalismo igualitário; Democracia constitucional; Estado democrático de direito; Pluralismo; Theory of justice; Equalitarian liberalism; Constitutional democracy; Democratic rule of law; Pluralism; ACCNPQ::Ciências Sociais Aplicadas::Direito